2016
DOI: 10.1101/cshperspect.a026427
|View full text |Cite
|
Sign up to set email alerts
|

MLL3/MLL4/COMPASS Family on Epigenetic Regulation of Enhancer Function and Cancer

Abstract: During development, precise spatiotemporal patterns of gene expression are coordinately controlled by cis-regulatory modules known as enhancers. Their crucial role in development helped spur numerous studies aiming to elucidate the functional properties of enhancers within their physiological and disease contexts. In recent years, the role of enhancer malfunction in tissue-specific tumorigenesis is increasingly investigated. Here, we direct our focus to two primary players in enhancer regulation and their role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 105 publications
3
123
0
Order By: Relevance
“…In mammals, there are at least nine H3K4-specific histone methyltransferases (HMTs), including mixed lineage leukemia (MLL) families consisting of MLL, MLL2, MLL3, MLL4, MLL5, SETD1A and SETD1B (6)(7)(8). The MLL family members, each possessing the highly conserved suppressor of variegation, enhancer of zeste, trithorax (SET) domain responsible for HMT activity, exist as distinct multiprotein complexes (namely complex of proteins associated with Set1, or COMPASS) with several common subunits, including Ash2, Wdr5, Rbbp5 and Dpy30 (9,10). MLLs have been credited as key H3K4 mono-, di-and trimethyltransferases at enhancers or promoters to facilitate gene expression (9,10).…”
Section: The Histone Methyltransferase Mixed Lineage Leukemia (Mll) 3mentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, there are at least nine H3K4-specific histone methyltransferases (HMTs), including mixed lineage leukemia (MLL) families consisting of MLL, MLL2, MLL3, MLL4, MLL5, SETD1A and SETD1B (6)(7)(8). The MLL family members, each possessing the highly conserved suppressor of variegation, enhancer of zeste, trithorax (SET) domain responsible for HMT activity, exist as distinct multiprotein complexes (namely complex of proteins associated with Set1, or COMPASS) with several common subunits, including Ash2, Wdr5, Rbbp5 and Dpy30 (9,10). MLLs have been credited as key H3K4 mono-, di-and trimethyltransferases at enhancers or promoters to facilitate gene expression (9,10).…”
Section: The Histone Methyltransferase Mixed Lineage Leukemia (Mll) 3mentioning
confidence: 99%
“…The MLL family members, each possessing the highly conserved suppressor of variegation, enhancer of zeste, trithorax (SET) domain responsible for HMT activity, exist as distinct multiprotein complexes (namely complex of proteins associated with Set1, or COMPASS) with several common subunits, including Ash2, Wdr5, Rbbp5 and Dpy30 (9,10). MLLs have been credited as key H3K4 mono-, di-and trimethyltransferases at enhancers or promoters to facilitate gene expression (9,10). Previous studies demonstrated that MLLs contribute to several types of cancers, acute myeloid leukemia, embryo development, circadian rhythm and brown adipocyte differentiation (11)(12)(13)(14)(15)(16)(17).…”
Section: The Histone Methyltransferase Mixed Lineage Leukemia (Mll) 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Utx/Kdm6a demethylase catalyzes “erasing” of the H3K27me3 mark at target genome sequences and therefore to contribute to activate gene transcription (Agger et al, 2008; Shilatifard, 2012; Sze & Shilatifard, 2016). By ChIP analyses, we determined that Utx is not bound to the CYP24A1 promoter in osteoblastic cells grown with a vehicle (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…In general, this epigenetic mark is deposited by the Polycomb Group Complex PRC2, predominantly by the activity of its catalytic subunit Ezh2, and represses transcription (Kazanets, Shorstova, Hilmi, Marques, & Witcher, 2016; Margueron et al, 2008). Reflecting a related dimension of epigenetic control, H3K27me3 can be erased from chromatin through the activity of the Utx/Kdm6a and Jmjd3/Kdm6b demethylases, which are often associated with nuclear complexes that activate transcription (Agger, Christensen, Cloos, & Helin, 2008; Shilatifard, 2012; Sze & Shilatifard, 2016). The expression of a large set of genes that are relevant for multiple physiological processes have been reported to be downregulated by PRC2‐Ezh2‐dependent enrichment of H3K27me3 (Margueron & Reinberg, 2011), further indicating that this epigenetic mark represents a critical component of the molecular mechanisms that control gene expression in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%